New pathobiochemical insights into dystrophinopathy from the proteomics of senescent mdx mouse muscle - Holland, Ashling; Dowling, Paul; Ohlendieck, Kay (Frontiers in Aging Neuroscience, 2014)
Primary abnormalities in the dystrophin gene cause X-linked muscular dystrophy, a highly progressive muscle wasting disorder of childhood. A spontaneous animal model of Duchenne muscular dystrophy is the mdx mouse, which presents a highly interesting phenotype that exhibits considerable variations in the degree of fibre degeneration in different subtypes of muscles. The idea that aging exacerbates the dystrophic mdx phenotype, as previously indicated by a large number of biochemical and cell biological studies, was clearly confirmed by comparative muscle proteomics. Here we outline recent findings of age-dependent changes in the dystrophin-deficient muscle proteome and contrast these results with the previously established proteomic profile of sarcopenic muscle. Besides comparable perturbations of various biochemical functions, especially striking are similarities in the cellular stress response associated with a drastic up-regulation of small αB-crystallin-like heat shock proteins. Hence, the comparison of large-scale proteomic data sets of natural muscle aging with dystrophic sarcopenia promises to shed light on the differential effect of sarcopenia of old age versus senescent abnormalities on a mutant dystrophic background.